Cast immobilization and addition of platelet rich plasma in intraarticular distal radius fracture resulting a better functional outcome to the internal fixation and radius union scorings system - Komang Indra Teguh Wisesa; I Ketut Siki Kawiyana; I Ketut Suyasa (DiscoverSys Inc., 2021)
Introduction: Intra-articular distal radius fracture is one of the most frequent injuries, especially in adults (20%). In this condition, anatomic reduction is required to reduce the possibility of complications, either with internal plate screw fixation (ORIF-PS) or conservatives such as the use of casting. Giving Platelet Rich Plasma (PRP) as one of the biologic agents to conservative management is expected to improve the outcome and become a promising alternative therapy.Methods: This study was an experimental study with a post-test control only group design on patients with intra-articular radius fractures at Sanglah General Hospital Denpasar during the period September 2019 to March 2020. The samples were selected by random sampling. Evaluation of the functional outcomes of the therapy given through DASH and RUSS scores was evaluated twice, namely at week 6 and week 12 post-therapy. Descriptive data analysis, General Linear Model (GLM) test and post hoc test were also carried out.Results: There were 45 patients divided into 3 groups; the first group of a plaster cast therapy and PRP injection, the second group of only plaster cast and the third group of ORIF. The first group showed better in DASH scores than the second group but not better than the third group, both at week 6 and 12. The results of the GLM and post hoc analysis also showed that the first group showed better RUSS scores than the second group.Conclusion: The addition of PRP has a better result than conservative therapy without PRP but ORIF still was the best therapy.